ENSURING FOOD SECURITY AS ONE OF THE PRIORITY NATIONAL INTERESTS - Grybko, Olga (Pressing Problems of Public Administration, 2021)
The state of food security guarantee in Ukraine on the basis of UN data is considered. Ukraine’s low rating in GFSI in terms of physical availability of food is explained by the state of its following components: high level of political instability; corruption risks; insufficient level of funding for research in the field of agriculture; unsatisfactory development of rural infrastructure.The European experience of building a food security system is analyzed. In the EU member States, the agriculture&food sector is an area of active regulation and protectionist practices, despite the fact that they generally consider market interference to be undesirable. The implementation of the common agricultural policy for about 60 years has allowed to achieve a high level of labor productivity in EU agriculture, which became possible due to long-term state support, first directly to producers and later to the “rural way of life”; to establish quality control and safety of high-efficiency food products, which now serves as a kind of technical barrier to entry into the European market of products of dubious quality, to significantly improve the standard of living in rural areas. It is expedient for Ukraine to bring its agricultural policy closer to the principles of the CAP, aimed at rural development, food safety and environmental protection. To improve Ukraine’s position in the global food security ranking, it is worth to pay attention to the development and implementation of a nutrition monitoring system, establishing a transparent mechanism for providing state guarantees of food availability, safety and quality, and revising Ukrainian food safety legislation in line with European practice.